Customized dynamic pricing of airline fare products. Issue 2 (April 2018) - Wittman, Michael; Belobaba, Peter
Abstract Firms practicedynamic pricing when they charge different customers different prices for the same products, as a function of an observable state of nature. In the airline industry, dynamic pricing has historically been limited by the capabilities of distribution systems, which require filing a finite set of fare products with fixed prices. However, advancements in airline distribution technology will soon allow the generation of "customized offers, " which could include a dynamically generated price. In this paper, we propose a heuristic for customized dynamic pricing of airfares when the observable state of nature includes an observation of passenger characteristics. We first introduce a general model for decoupling the customized offer generation problem from the well-studied airline revenue management problem. After generating a baseline assortment of fare products and observing the characteristics of a passenger's request, an airline can choose to customize that passenger's offer by dynamically incrementing or discounting the prices that would ordinarily be offered. The methodology could be applied with existing airline revenue management methods, and would be compatible with IATA's New Distribution Capability (NDC). For implementation, we propose a straightforward heuristic approach based on simple estimates of passenger willingness-to-pay distributions. The heuristics are simulated in the Passenger Origin–Destination Simulator, a complex airline revenue management simulation environment that takes into account passenger choice and competition. The results show that the heuristics can lead to revenue gains of up to 3–4% when practiced by one airline. Furthermore, the heuristics remain revenue positive in competitive environments.